Military aircraft - Loves, June.; Lucia, Lorenzo (Broomall, PA : Chelsea House Publishers, 2002)
Provides photographs and information about different types of military aircraft and how they have been used throughout history, looking at airships, fighters, bombers, and helicopters; and includes a flight time line, and a glossary.
"First published in 2000 by Macmillan Education Australia ... South Yarra, Australia"--T.p. verso.
Includes index.
Library Talk.
5.5
3-6
Keywords: Airplanes, Military -- Juvenile literature; Flight -- Juvenile literature; Airplanes, Military; Flight; Flight; Military airplanes